Signifikansi Paradigma Pendidikan Kritis dalam Dunia Posrealitas - Gianto, Gianto (Nadwa, 2012)
New world as a result of the development of science and technology mutakhir makes sign no longer reflect reality. Representation is no longer associated with the truth. The new world was built by various forms of distortion of reality, free game mark, meaning irregularities and artificiality meaning. The new world was built by many reality distortions, the free sign game, the deviation and appear-ance of meaning. A new reality world draws a metamorphosis which is got by human, from what mentioned as a reality condition, turn to post-reality. The post-reality will not effect at all to human if the critical awareness of human is kept on. Yet, if the critical awareness of human has been eroded, the human has artificial awareness. Actually, the post-reality is not a threat for humanâs life if the critical awareness is kept on. Yet, if the critical awareness of human is erod-ed, human will be pressed and dominated by post-reality world.